Optimal adaptive IMRT strategy to spare the parotid glands in oropharyngeal cancer. Issue 1 (July 2016) - Zhang, Pengcheng; Simon, Antoine; Rigaud, Bastien; Castelli, Joël; Ospina Arango, Juan David; Nassef, Mohamed; Henry, Olivier; Zhu, Jian; Haigron, Pascal; Li, Baosheng; Shu, Huazhong; De Crevoisier, Renaud
Abstract: Purpose: In oropharyngeal cancer adaptive radiation therapy (ART), this study aimed to quantify the dosimetric benefit of numerous replanning strategies, defined by various numbers and timings of replannings, with regard to parotid gland (PG) sparing. Material and methods: Thirteen oropharyngeal cancer patients had one planning and then six weekly CT scans during the seven weeks of IMRT. Weekly doses were recalculated without replanning or with replanning to spare the PG. Sixty-three ART scenarios were simulated by considering all the combinations of numbers and timings of replanning. The PG cumulated doses corresponding to "standard" IMRT and ART scenarios were estimated and compared, either by calculating the average of weekly doses or using deformable image registration (DIR). Results: Considering average weekly doses, the mean PG overdose using standard IMRT, compared to the planned dose, was 4.1 Gy. The mean dosimetric benefit of 6 replannings was 3.3 Gy. Replanning at weeks 1, 1–5, 1–2–5, 1–2–4–5 and 1–2–4–5–6 produced the lowest PG mean doses, 94% of the maximum benefit being obtained with 3 replannings. The percentage of patients who had a benefit superior to 5 Gy for the contralateral PG was 31% for the three-replannings strategy. The same conclusions were found using DIR. Conclusion: Early replannings proved the most beneficial for PG sparing, three replannings (weeks 1–2–5), representing an attractive combination for ART in oropharyngeal cancer.